Divine Film Comedies: Biblical Narratives, Film Sub-Genres, and the Comic Spirit - Detweiler, Craig (The journal of religion and film, 2017)
This is a book review of Terry Lindvall, J. Dennis Bounds and Chris Lindvall, Divine Film Comedies: Biblical Narratives, Film Sub-Genres, and the Comic Spirit, New York : Routledge, 2016.